Prevalence of Mental Health Problems in Working and Non-Working Adolescents: A Comparative Study - Niaz, Aysha; Zahra, Syeda Mehreen; Naeem, Fatima (Journal of Pakistan Psychiatric Society, 2020)
Objective: to find out the prevalence of Mental Health Problems in working and non-working Adolescents.Study Design: Cross sectional research design was used.Place and Duration of the study: the duration of the study was January- August 2018.Subject and Method: 200 adolescent boys and girls (100 working and 100 non-working Adolescent), with the age ranges from 11 to 18 years (M, 14.52, SD 1.73). Non-working Adolescents were selected from 3 different schools of Lahore enrolled in 8th-10thgrade. The sample of Working adolescent (boys=50, girls=50) was taken from different canteens and restaurants of Lahore, through purposive sampling strategy. After selection participants were given a 42 items, Depression, Anxiety Stress Scale (DASS), intended to assess three construct namely, depression, stress and anxiety, along with demographic performa.Results: the results showed that the frequency of depression (28%), anxiety (30%) and stress (30%) in non-working adolescents, whereas the frequency of depression (34%), anxiety (38%) and stress (46%) in working adolescents. The result showed that working adolescents experience more stress parallel to non-working adolescents.Conclusion: The study shows significant presence of depression, anxiety and stress in working and Non-working Adolescents. Therefore, it is deem necessary for all stakeholders to devise strategies to reduce mental health problems, before it aggravates and turns into serious psychopathology.